Low‐δ18O Rhyolites From the Malani Igneous Suite: A Positive Test for South China and NW India Linkage in Rodinia - Wang, Wei; Cawood, Peter A.; Zhou, Mei‐Fu; Pandit, Manoj K.; Xia, Xiao‐Ping; Zhao, Jun‐Hong (Geophysical research letters, 2017)
The Malani igneous suite (MIS) in NW India represents one of the best preserved silicic large igneous provinces. Voluminous silicic lavas of the MIS erupted between ~780–750 Ma. Zircon grains from rhyolite and dacite lavas have oxygen isotopic compositions that include depleted (δ18O = 4.12 to −1.11‰) and enriched (δ18O = 8.23–5.12‰) signatures. The low‐δ18O zircon grains have highly radiogenic Hf isotopic compositions (ƐHf(t) = +13.0 to +3.6), suggesting high‐temperature bulk cannibalization of upper level juvenile mafic crust as an essential mechanism to produce the low‐δ18O felsic magma. Xenocrystic zircon grains in dacites have high δ18O and low ƐHf(t) values for magmas older than 800 Ma, reflecting a dramatic transition in tectono‐thermal regime in NW India during 800–780 Ma. A synchronous transition also occurred in south China and Madagascar, suggesting a spatially linked geodynamic system. NW India and south China together with Madagascar and the Seychelles lay either along the periphery of Rodinia or outboards of the supercontinent with the age of convergent plate margin magmatism coinciding with breakup of the supercontinent. Key Points δ18O depleted rhyolite from the Malani Igneous Suites (MIS) in NW India Significant shift from magmatism with mantle‐like δ18O‐ƐHf(t) values to low 18O but juvenile magmatism at 800–780 Ma Similar tectono‐thermal transition occurred in NW India, south China, and Madagascar at 800–780 Ma